Intravenous lidocaine for gut function recovery in colonic surgery: a health economic evaluation of the ALLEGRO randomised clinical trial - John Norrie; Graeme Maclennan; Lorna Aucott; Karen Innes; Andrew Stoddart; Seonaidh Cotton; Hugh Paterson; Doug Speake; Robert Arnott; Thenmalar Vadiveloo; Marek Atter; Angie Balfour; et al. (BMJ Open)
Objectives To compare costs, health outcomes and cost-effectiveness of using intravenous lidocaine (bolus given at induction of anaesthesia, followed by infusion for 6–12 hours) during colorectal surgery to improve the return of gastrointestinal function.Design Within-trial planned analysis of data from a randomised controlled trial using an intention-to-treat approach.Setting 27 hospitals from across the UK.Participants 557 patients aged 25–91 having minimally invasive elective colorectal resection.Intervention A 1:1 randomisation between intravenous lidocaine and placebo, minimised for age (<50 years, 50–74 years, ≥75 years), gender, and trial centre.Primary outcome measures Mean differences between trial arms in 30-day and 90-day quality-adjusted life-years (QALYs) and 30-day total National Health Service costs, as well as the 30-day incremental cost-effectiveness ratio.Results Compliance and data quality were high. Intravenous lidocaine is associated with differences of £38 (95% CI: −£463, £589) in total 30-day costs, −0.0005 (95% CI: −0.0027, 0.0015) in 30-day QALYs and −0.0008 (95% CI: −0.0066, 0.0048) in 90-day QALYs. No large, statistically significant or meaningful differences in primary or secondary outcome measures between trial arms were detected, other than for the intervention costs.Conclusion Intravenous lidocaine is not found to impact costs or health outcomes for patients undergoing colorectal surgery. In the absence of a clinical effect, disinvestment from perioperative lidocaine could save costs associated with infusion monitoring.Trial registration number International Standard Randomised Controlled Trial Number 52352431.